Pyrolysis of sandbox (Hura crepitans) shell: Effect of pyrolysis parameters on biochar yield - F.A. Ola; S.O. Jekayinfa (Research in Agricultural Engineering, 2015)
Pyrolysis of sandbox shell was carried out with the aim of investigating the effect of pyrolysis parameters on the pyrolysis process and identifies production conditions for the yield of biochar. Parameters investigated were heating temperature (400, 500 and 600°C), heating time (10, 20, and 30 min) and particle size of feedstock (0-1.0, 1.0-2.5 and 2.5-5.0 mm) in a laboratory batch pyrolysis process. The experiment was designed by applying response surface methodology through a three-factor full factorial design. The quadratic polynomial model obtained explains adequately the modelled response with coefficient of correlation, R2 value of 0.8698. All the three variables significantly affected the biochar yield from sandbox shell, with heating temperature being the most effective followed by heating time and particle size of feedstock. Maximum biochar yield of 39.65% wt. occurred at 400°C heating temperature and 10 min heating time with 1.0-2.5 mm particle size.